2002
DOI: 10.2337/diacare.25.12.2197
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Childhood Type 1 Diabetes in Children Born After 1985

Abstract: OBJECTIVE—The incidence rate of childhood type 1 diabetes is thought to be increasing; however, Danish studies have not confirmed this. Using a national diabetes register initiated in 1996 and two previous regional incidence studies, we studied the age-specific incidence of type 1 diabetes over 30 years. Here, we describe the incidence rates of type 1 diabetes in Danish children from 1996 to 2000 and evaluate trends in age-specific incidence rates from 1970 to 2000. RESEARCH DESIGN AND METHODS—A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
7
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
7
51
7
1
Order By: Relevance
“…The incidence rates in the younger age group in this study show a similar pattern to those reported in studies from the Danish Childhood Diabetes Register (DSBD), with a peak among girls about age 12 years and about 15 years for boys [17]. Furthermore, a study using pharmacological data to identify the diabetes population in the county of Fyn has also found an increased prevalence and decreased mortality rates in the same period [18].…”
Section: Discussionsupporting
confidence: 85%
“…The incidence rates in the younger age group in this study show a similar pattern to those reported in studies from the Danish Childhood Diabetes Register (DSBD), with a peak among girls about age 12 years and about 15 years for boys [17]. Furthermore, a study using pharmacological data to identify the diabetes population in the county of Fyn has also found an increased prevalence and decreased mortality rates in the same period [18].…”
Section: Discussionsupporting
confidence: 85%
“…In this observational study, we did not have any data on exposure, either genetic or environmental. The markedly increased risk for siblings born in 1980 or later is in keeping with the incidence trend data from Finland and several European countries (23,(33)(34)(35). Although the data show differences in the risk of type 1 diabetes between birth cohorts, there might be some underestimation in the risk of type 1 diabetes in the earliest birth cohort.…”
Section: Type 1 Diabetes Incidence In Finnish Siblingssupporting
confidence: 81%
“…The incidence of type 1 diabetes before 15 years of age is increasing [1,2], especially for children diagnosed at an early age [3][4][5][6][7]. HLA susceptibility genes are strongly associated with type 1 diabetes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%